The effects of Clitoria ternatea extract on zebrafish model of Alzheimer’s disease : a neurobehavioural study - Muhammad Danial bin Che Ramli,; Nur Arissa Syazwani Md Nazrey,; Mahathir Mohd Uzid,; Anita Zara Weinheimer,; Nur Batrisyia Nizam,; Nadhratun Nabila Mazlan,; Nurshafiqah Najihah Mohd Mizan,; Hussin Muhammad,; Mohamad Anuar Ahad,; Mohamad Azmeer Effendy, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease that is currently affecting 40-50 million people worldwide. It is generally recognized from its main symptom dementia, in which the patient undergoes a progressive decline in their cognitive memory. Recent studies have shown that medicinal plants such as Clitoria ternatea equipped with antioxidant properties has high potential in treating AD. The study was conducted using zebrafish model of AD induced with aluminium chloride for 28 days. The treatment dose of C. ternatea extract (4.34 mg/L) was then given for 14 days. The behaviour of the zebrafish were evaluated through memory testing by using a T-maze test and novel tank diving test. Histological studies were also performed. 50% of the zebrafish tested showed improvement in memory through the T-maze test after treatment with C. ternatea extract. Zebrafish model of AD treated with C. ternatea extract also shows a decrease in anxiety in the novel tank diving test. A significant increase of purkinje cells were also observed from the histological study after treatment with C. ternatea extract. Nucleus elongation of oligodendrocytes from zebrafish model of AD induced with aluminium chloride were improved when treated with the C. ternatea extract. In conclusion, it was found that C. ternatea extract exhibits strong potential for treating zebrafish model of AD induced with aluminium chloride.